Investigations of Particle-Initiated Insulation Breakdowns in Bearings - Joshi, Abhishek; Blennow, Jörgen (Journal of Renewable Energy, 2019)
Early failures in bearings of wind turbine drivetrains have increased after introduction of power electronic switches, which leads to shaft voltages and bearing currents. In presence of voltage, a rupture of bearing insulation could occur due to several plausible electro-physical mechanisms viz., asperities, electric breakdowns, particles, etc. The flow of high amperage current through the bearing during a breakdown mechanism could lead to early failures. Our aim is to understand the electrical behaviour of a bearing and elaborate by an equivalent electric circuit model, emphasizing on particle-initiated breakdowns. In presence of a shaft voltage, the particles form a path of low resistance through the bearing and results in flow of shaft or bearing currents, which could cause pre-mature failure of the bearing. Particles such as Arizona Test Dust (ATD), carbon black, aluminium powder and fine iron powder were mixed in lubricant at particle concentrations ranging between 7.5 mg/L and 150 mg/L. The breakdown characteristics of electrical insulation of the bearing during a given test is quantified as time of conduction, which is expressed as a percentage of the time the bearing is in the conducting state during a test. An investigation of time of conduction for different lubricant samples was conducted along with studying the effects of start and stops of the rotating shaft. The electrical conductive nature of the particle played no role in breakdown of bearing voltage. At a fixed concentration of 150 mg/L, the insulation breakdown events were highest in lubricant with ATD, followed by iron powder, aluminium power and carbon black particles. The time of conduction increases up to 24 times for the same test lubricant, as the particle concentration was increased from 7.5 mg/L to 150 mg/L. The current activity reduced to almost half in the test after stopping the shaft rotation. The resistance of bearing during insulation breakdown events is highest for aluminium powder, followed by fine iron powder, carbon black and ATD.